Formulasi eyeshadow kombinasi umbi bit (Beta vulgaris L.) dan rimpang kunyit (Curcuma longa L.) dalam perbandingan ekstrak dan nanoekstrak - Sihotang, Laura Indah Restu; Dalimunthe, Gabena Indrayani; Lubis , Minda Sari; Yuniarti, Rafita (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Eyeshadow is an eye cosmetic that contains coloring agents to color effects and change the appearance. Some eyeshadow products use synthetic dyes that have a negative impact, so it is important to use safe dyes such as beetroot to produce a red color and turmeric rhizome to produce a yellow color. Turmeric rhizome yellow color. Nanoparticle-based cosmetics have advantages and can penetrate cell walls more effectively. This study aims to determine whether beetroot and turmeric rhizome extracts meet the requirements of nano extracts. Nano extracts determine the color difference at each concentration in the extracts and nano extracts as colorants for eyeshadow preparations, and choose the color of the extracts and nano extracts in eyeshadow preparations with certain concentrations that can meet the physical quality and favored by panels. This research method is True Experimental, and the research design used is a post-test-only control group design. The research design used was a post-test-only control group design. Independent variables are variations in the concentration of the combination of extracts and nano extracts of beetroot and turmeric rhizomes and eyeshadow formulations of various concentrations. Turmeric rhizome and eyeshadow formulations of multiple concentrations. The dependent variables are simplicity characteristics, phytochemical screening, particle uniformity characteristics, nano extract, and various tests. Nano extracts and various physical quality inspection tests of eyeshadow. The results showed that the beetroot and turmeric rhizome extracts met the requirements of nanoextracts with a particle size of beetroot 261 nm and turmeric rhizome 203 nm. Eyeshadow preparations containing a combination of beetroot and turmeric rhizomes in extracts and nano extracts have different colors: F1 is pink, F2 is light brown, F3 is Salem peach, F4 is peach pink, F5 is brown, and F6 is Salem pink. All eyeshadow preparation formulas meet the physical quality requirements, and F5 and F6 are the most preferred formulas for volunteers because they provide attractive colors.